Language of Space in Live of Saint Erasmus - B. B. Ilyin (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The article is devoted to the consideration of the category of space in the Old Russian text. The text of the live of Erasmus was used for analysis.  The novelty of the work lies in the reference to the text of the monument, in which the category of space was not previously considered.  The research is based on nominative vocabulary with spatial meaning. In the course of consideration, various types of spaces in the live were identified: real-geographical, urban, sacred, biblical, symbolic. The axiological attitude of the genre becomes important for understanding space in live: space is interpreted in a religious-symbolic way. It is showed in the article that the living space is built horizontally and vertically. It is emphasized that the horizontal movement of the hero reflects the movement of the hero in the geographic space. The path is understood both literally and metaphorically. Particular attention is paid to the opposition of the top and bottom that is significant for the text of the live: the top is associated with the divine, the bottom is associated with the concept of the devil. It shows how the biblical space is created by references to the biblical text. The symbolic space is also associated with vertical opposition and has a religious and ethical interpretation: the image of the city of the saint appears, intended for the righteous. The axiological attitude is also reflected in the transformation of space or its overcoming when describing some miracles in the text.